Investigate Live Streaming Commerce on Tiktok as Trends New Online Shopping: Exploration Perception and Intention Consumer - Widiani, I Gusti Agung Ayu Dewi; Maradona, Agus Fredy (International Journal of Science and Society, 2024)
The Covid-19 pandemic has changed the way people interact with digital technology. The increased use of the internet is not limited to activities such as searching for information and communicating; it has also entered the realm of the economy with online trading of goods and services. Social media platforms like TikTok have become places not only for social interaction but also for direct purchasing. Guided by the Technology Acceptance Model and the Theory of Planned Behavior, this study explores consumers' perceptions and intentions regarding using the live-streaming commerce feature on TikTok for purchasing goods. Through semi-structured interviews with consumers who actively use this feature to shop for products, the research findings indicate that consumers have perceptions about using the live-streaming commerce feature on TikTok. External influences can affect consumers' interest in using TikTok's live-streaming commerce feature. Some barriers affect consumers' intentions to use the live-streaming commerce feature on TikTok. There is also perceived ease of use and usefulness in using TikTok's live streaming commerce feature. The implications of this research can help platform developers and businesses better understand the needs and preferences of consumers when using the live streaming commerce feature on TikTok and adjust their marketing strategies accordingly